AH-03 Anatomical Characteristic of Forelimb Skeleton of Sumatran Rhino (Dicerorhinus sumatrensis) - Nurhidayat Nurhidayat; Eni Puji Lestari; Chairun Nisa'; Danang Dwi Cahyadi; Supratikno Supratikno (Media Veteriner, 2015)
Anatomical Characteristic of Forelimb Skeleton of Sumatran Rhino        (Dicerorhinus sumatrensis)